2020
DOI: 10.1093/eurheartj/ehaa689
|View full text |Cite
|
Sign up to set email alerts
|

Vupanorsen, an N-acetyl galactosamine-conjugated antisense drug to ANGPTL3 mRNA, lowers triglycerides and atherogenic lipoproteins in patients with diabetes, hepatic steatosis, and hypertriglyceridaemia

Abstract: Aims  Loss-of-function mutations in ANGPTL3 are associated with beneficial effects on lipid and glucose metabolism and reduced risk of coronary artery disease. Vupanorsen (AKCEA-ANGPTL3-L Rx ) is an N-acetyl galactosamine-conjugated antisense oligonucleotide targeted to the liver that selectively inhibits angiopoietin-like 3 (ANGPTL3) protein synthesis. Methods and results  This was a double-blind, placebo-controlled, dose-ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
169
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 212 publications
(177 citation statements)
references
References 18 publications
7
169
1
Order By: Relevance
“…Recent evidence has confirmed the prominent role that inhibitors of ANGPTL3 have in the removal of triglycerides-rich particles, LDL-C and apo B levels, probably due to an increased clearance of apo B containing lipoproteins and their remnants [ 33 ]. Monoclonal antibodies and antisense oligonucleotides that target ANGPTL3, and 4 are potentially an efficient therapeutic strategy for cardiovascular risk reduction in hypertriglyceridemia, especially in patients with FHTG [ 55 , 56 ]. The results suggest that this molecule may be involved in the pathogenesis of FHTG and its measurement may be helpful for diagnosis (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence has confirmed the prominent role that inhibitors of ANGPTL3 have in the removal of triglycerides-rich particles, LDL-C and apo B levels, probably due to an increased clearance of apo B containing lipoproteins and their remnants [ 33 ]. Monoclonal antibodies and antisense oligonucleotides that target ANGPTL3, and 4 are potentially an efficient therapeutic strategy for cardiovascular risk reduction in hypertriglyceridemia, especially in patients with FHTG [ 55 , 56 ]. The results suggest that this molecule may be involved in the pathogenesis of FHTG and its measurement may be helpful for diagnosis (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Although it has been approved for use in Europe, it causes thrombocytopenia. Vupanorsen is a second generation N-acetyl galactosamine-conjugated antisense oligonucleotide derivative targeting hepatic ANGPTL3 mRNA that has greater potency allowing 20-to 30-fold lower dosing, fewer side effects and similar effects on APOC3 and triglyceride to that reported with volanesorsen (133).…”
Section: Targeting Lpl Regulatorsmentioning
confidence: 99%
“…A strong correlation was seen among circulating ANGPTL3 and ANGPTL8 indicating a possible co-secretion of the two proteins [ 99 , 100 ]. Recently, a phase II trial has tested vupanorsen [ 101 ], an ANGPTL3 antisense oligonucleotide, in T2DM patients [ 101 ]. Preliminary results of the study found no significant change in the HOMA index, a widely used index for insulin resistance [ 102 ].…”
Section: Clinical Conditions Linking Angptls and Adipose Tissue Dymentioning
confidence: 99%
“…Reported evidence might not be reliable. Morinaga et al using a self-developed and controlled ANGPTL8 assay found higher circulating levels of ANGPTL8, in T2DM patients, associated with increased levels of LDL-C, TGs, and reduced HDL-C [ 101 ]. Interestingly, differences in ANGPTL8 expression are observable in obese vs. non-obese patients: in obese patients, VAT shows increased levels of ANGPTL8 in the nucleoplasm, while serum levels remain similar to non-obese controls [ 69 ].…”
Section: Clinical Conditions Linking Angptls and Adipose Tissue Dymentioning
confidence: 99%
See 1 more Smart Citation